KEHIDUPAN MEMBIARA DAN JEBAKAN TAKDIR: SUBJEKTIVITAS ROMO YB MANGUNWIJAYA DALAM PERSPEKTIF SLAVOJ ŽIŽEK - Taum, Yoseph Yapi (Sunan Kalijaga State Islamic University Yogyakarta, 2023)
The monastic life for celibate individuals is not a problem-free life choice. As human beings, individuals who choose the monastic life face various biological, sociological, and psychological upheavals that are not easily overcome. These upheavals can lead to a crisis of faith. This study aims to uncover the issues faced by celibate individuals as depicted in the novel